THE EFFECT OF GINGER RHIZOMES (Curcuma xanthorriza Roxb.) TOWARDS THE NUMBER OF OVARIAN FOLLICLES OF FEMALE MICE (Mus musculus) EXPOSED TO MONOSODIUM GLUTAMAT (MSG) - Dianti, Meilina Ratna (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2017)
Monosodium Glutamat activates an axis ablation in arcuate nucleus hypothalamus which happens to possibly initiate malfunctions in Hipothalamic Pituitary Adrenal axis. Yet, it is known that hypothalamus produces Gonadotropin Releasing Hormone which is able to stimulate the secretion of Gonadotropin Follicle Stimulating Hormon and Luteinizing Hormone from the anterior pituitary gland. These two hormones, however, are essentials for the development of gonad and during the cycles of oogenesis. Hence, any malfunctions resided in the human’s hypothalamus can possibly put endocrine gland into troubles, such as reproduction hormones which affect the workings of gonad. Therefore, the extract of Temulawak is promoted to be the attempt to resolve the issue for its antioxidant properties. Temulawak extract contains antioxidant, properties for as much as 87.01 ppm, according to Rosidi research’s result, analyzing the Temulawak’s potentials. The amount of antioxidant found Temulawak extract is categorized as active and applicable as natural antioxidant source. However, this research adopts true experimental post-test only control group design. It includes 5 (five) groups of female mice as which are K1 (CMC), K2 (CMC+MSG), P1 (MSG+0.4 mg Temulawak extract), P2 (MSG+0.8 MG Temulawak extract), P3 (MSG+1.2 mg Temulawak extract). In addition, the mice’s ovaries are removed to be subsequently tested using Hematoxillin-Eosin and the ovaries’ follicles quantity is observed and counted. The data is analyzed using One Way ANOVA. The research finally comes with a result showing that there are not any significant differences discovered from the ovaries’ follicles quantity from the five tested groups (p0.05). Therefore, it is implied that Temulawak extract does not provide any influential results to the house mice’s ovaries’ follicles quantity which has been exposed to MSG. Keywords: Monosodium Glutamate (MSG), Temulawak (Curcuma xanthorriza Roxb.), Ovarian follicles quantity